Perceptions of South African Police Service officials regarding the implementation of sector policing in Limpopo Province - Niekerk, Rhona van (Acta criminologica, 2019)
The purpose of this article is to focus on the level of implementation of sector policing in South Africa in terms of Sector Policing National Instruction 3/2013. The contribution also focuses on the perceptions of South African Police Service officers responsible for implementing sector policing at police stations according to the guidelines of National Instruction 3 of 2013. In a study conducted by van Niekerk (2016), the qualitative research results indicate challenges preventing police officials from adequately implementing Sector Policing National Instruction 3/2013. A noteworthy number of station commanders and sector commanders of urban and rural police stations stated that sector policing, as defined by Sector Policing National Instruction 3/2013, was a pro-active partnership policing approach and a crime reduction strategy but emphasised that successful implementation of sector policing depends on certain conditions. An overview of some of their responses regarding these conditions will be highlighted.